2010
DOI: 10.2174/18748368010040100017
|View full text |Cite
|
Sign up to set email alerts
|

A Decision Support Tool for Cost Mastering in Urban Self-Construction: The Case of Cameroon

Abstract: Abstract:The critical housing shortage in cities of the developing countries like Cameroon generates an ever-growing desire to increase housing supply. The main group of actors in this domain are by and large the formal sector, while the informal sector is still inactive. Because of the legalities and costs associated with the formalities surrounding the provision of formal housing, the majority of urban residents are bypassed by the formal housing policies. The only alternative for them is thus self-construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…Finally, the analytical methods make it possible to refine the accuracy of the costs at the preliminary design stage but require a lot of detailed information. The decomposition of the project into its different sub-structures and different trades allows the authors (Pettang C. et al, 1997;Louzolo-Kimbembé and Pettang, 2006;Manjia et al, 2010;2011;2012) to exploit the matrix approach to improve the efficiency and speed of cost calculations analytically. This matrix approach leads to the decomposition of total construction cost into three fundamental elements, namely, material, labour, and management means, which is represented as follows:…”
Section: Review Of the Concepts Of Cost And Time Uncertainties In A C...mentioning
confidence: 99%
“…Finally, the analytical methods make it possible to refine the accuracy of the costs at the preliminary design stage but require a lot of detailed information. The decomposition of the project into its different sub-structures and different trades allows the authors (Pettang C. et al, 1997;Louzolo-Kimbembé and Pettang, 2006;Manjia et al, 2010;2011;2012) to exploit the matrix approach to improve the efficiency and speed of cost calculations analytically. This matrix approach leads to the decomposition of total construction cost into three fundamental elements, namely, material, labour, and management means, which is represented as follows:…”
Section: Review Of the Concepts Of Cost And Time Uncertainties In A C...mentioning
confidence: 99%
“…Louzolo-Kimbembé & Pettang (2006) reported the lack of efficient cost planning techniques. Abanda et al (2011), Manjia et al (2010) reported the lack of labour cost estimating tools. Recently, Fombe & Ntani (2012) argued for the necessity to deal with huge amount of waste being generated from construction projects.…”
Section: An Overview Of Construction Practice In Cameroonmentioning
confidence: 99%
“…The afore-mentioned weaknesses have already been dealt with in developed countries (Cheung et al, 2012;Shen & Issa, 2010), although considerable progress is still being made. Furthermore, despite these efforts by different researchers (Louzolo-Kimbembé & Pettang, 2006;Abanda et al, 2011;Manjia et al, 2010;Fombe & Ntani, 2012) to address various aspects of construction project management, studies about integrated or collaborative project delivery in construction environments are rare. The few that exist cover collaborative community project delivery of some infrastructure projects in Cameroon (Njoh, 2002;2003).…”
Section: An Overview Of Construction Practice In Cameroonmentioning
confidence: 99%